Performance Assessment and Optimization of Biomass Steam Turbine Power Plants by Data Envelopment Analysis - Ueasin, Nattanin; Wongchai, Anupong; Nonthapot, Sakkarin (International Journal of Energy Economics and Policy, 2015)
As rice husk is abundantly natural resource in Thailand, it has been used as the biomass energy resource in the stream turbine power plants, in particular to Very Small Power Producers (VSPPs). The VSPPs' plants produced by rice husk is generally found in many regions of Thailand, however its performance efficiency and optimization has never been assessed at any level. This study aimed to fulfill this gap by adopting the method of Data Envelopment Analysis (DEA) to relatively measure the performance efficiency of the decision making units (DMUs), as well as to adjust input surpluses found in order to maximize the overall efficiency scores. The secondary data recorded in 2012 were collected from the power policy bureau of Thailand and Energy for Environment Foundation, totally 47 rice husk steam turbine power plants. The empirical results showed that a CRS-DEA and VRS-DEA model performed efficiency scores at 0.874 and 0.882, respectively. The input surpluses of capacity and purchasing cost of rice husk were emphasized to increase its unit efficiency. Achieving the Thai government's aim of sustainable, renewable energy would boost up many utility plants to use rice husk for electricity generation in the nearer future. Keywords: Biomass; Data Envelopment Analysis; Stream Turbine JEL Classifications: Q420; M110